Islamic Banks in the Digital Age : Balancing Innovation with Sharia Principles - Afdawaiza, Afdawaiza; Mas’ud, Riduan; Manulandong, Shahid Q. (IKONOMIKA, 2024)
As digital technologies evolve at an unprecedented pace, Islamic banks face the dual challenge of embracing innovation while maintaining strict adherence to Sharia principles. This article examines the strategies employed by Islamic banks to balance technological advancements with Sharia compliance, focusing on the integration of digital tools such as blockchain, artificial intelligence, and mobile banking. Through a review of current practices and case studies, this study identifies key factors that enable Islamic banks to innovate without compromising their ethical and religious obligations. The analysis highlights the potential benefits of digital transformation, including enhanced customer engagement, improved operational efficiency, and greater financial inclusion, while also addressing the risks associated with technological adoption, such as regulatory challenges and ensuring Sharia compliance in a rapidly changing digital landscape. The findings underscore the importance of a thoughtful, collaborative approach among technologists, Sharia scholars, and regulators to enable Islamic banks to navigate the digital age successfully. Achieving this balance is vital not only for maintaining competitiveness but also for upholding the integrity of Islamic finance.